NPC1161B, an 8-Aminoquinoline Analog, Is Metabolized in the Mosquito and Inhibits Plasmodium falciparum Oocyst Maturation - Hamerly, Timothy; Tweedell, Rebecca E.; Hritzo, Bernadette; Nyasembe, Vincent O.; Tekwani, Babu L.; Nanayakkara, N. P. Dhammika; Walker, Larry A.; Dinglasan, Rhoel R. (Frontiers in Pharmacology, 2019)
Malaria is a major global health threat, with nearly half the world’s population at risk of infection. Given the recently described delayed clearance of parasites by artemisinin-combined therapies, new antimalarials are needed to facilitate the global effort toward elimination and eradication. NPC1161 is an 8-aminoquinoline that is derived from primaquine with an improved therapeutic profile compared to the parent compound. The (R)-(-) enantiomer (NPC1161B) has a lower effective dose that results in decreased toxic side effects such as hemolysis compared to the (S)-(+)-enantiomer, making it a promising compound for consideration for clinical development. We explored the effect of NPC1161B on Plasmodium falciparum oocyst and sporozoite development to evaluate its potential transmission-blocking activity viz. its ability to cure mosquitoes of an ongoing infection. When mosquitoes were fed NPC1161B 4 days after P. falciparum infection, we observed that total oocyst numbers were not affected by NPC1161B treatment. However, the sporozoite production capacity of the oocysts was impaired, and salivary gland sporozoite infections were completely blocked, rendering the mosquitoes non-infectious. Importantly, NPC1161B did not require prior liver metabolism for its efficacy as is required in mammalian systems, suggesting that an alternative metabolite is produced in the mosquito that is active against the parasite. We performed LC-MS/MS analysis of methanol extracts from the midguts of mosquitoes fed on an NPC1161B (434.15 m/z)-treated blood meal and identified a compound with a mass of 520.2 m/z, likely a conjugate of NPC1161B or an oxidized metabolite. These findings establish NPC1161B, and potentially its metabolites, as transmission-blocking candidates for the treatment of P. falciparum.